Peningkatan Perekonomian Masyarakat dalam Bidang Industri Pada Masa Pandemi Covid19 di Desa Karang Kedawang - Irma Ardiawati; Khoirotul Izzah (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2020)
Improving the economy of the community is an activity carried out by the community to obtain goods and services to meet daily needs. In this report entitled "Improving the economy of the Community in the field of Industry During the Pandemic of Karang Kedawang Village". Unemployment is one of the problems that have arisen this year, both at the regional level and at the state level. Unemployment is affected by economic changes in society. The problem will be studied in this study by describing the effect of economic growth on the unemployment of kedawang coral village. The purpose of research is to know and analyze the effect of economic growth on the unemployment of kedawang coral villages. This type of research is quantitative research, namely with data collection methods. With the impact of pandemics in all regions, namely in Indonesia, the complaint that I hear most often is the ECONOMY because most of the jobs in my village are trading (home industry), not only with traders, even the community / individual workers (factory curry) in my village have the same complaint that is the economy. Because the economy is one of man's efforts to survive. From the results of this research, the mojokerto district government is expected to provide jobs in order to absorb labor, and is expected to be able to overcome the complaints of the entire community with economic congestion during the covid-19 pandemic.